Pengaruh biaya pemasaran dan biaya produksi terhadap laba bersih pada Astra Agro Lestari tbk periode 2019—2024 - Reza Kurniawan; Muhammad Ardi Nupi Hasyim (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This study aims to determine the effect of marketing costs and production costs on net profit, both partially and simultaneously, at PT Astra Agro Lestari Tbk over a six-year period, namely from 2019—2024. The research method used in this study is a quantitative method with descriptive and associative research types. The data used are secondary data obtained from the financial statements of PT Astra Agro Lestari Tbk. The results of the study indicate that partially the marketing cost variable has no effect, production costs have an effect. In addition, simultaneously the marketing cost and production cost variables do not affect net profit.